Frequency Speed Control of Rotary Travelling Wave Ultrasonic Motor Using Fuzzy Controller - Kebbab, F. Z.; Belkhiat, D. E. C.; Jabri, D.; Belkhiat, S. (Engineering, Technology & Applied Science Research, 2018)
This paper proposes frequency speed control of rotary travelling wave ultrasonic motor (TWUSM), type Daimler Benz AWM90-X motor. The control characteristics of TWUSM are complicated, highly nonlinear and varying in time. This can lead to deterioration of the performance of conventional controller such as proportional integral (PI). In order to achieve high control performance of the TWUSM, fuzzy logic controller (FLC) has been designed and compared to the conventional PI controller. To validate the performance of the proposed FLC, simulation of the speed response has been performed and analyzed for a varying load. The simulation results show that the FLC has smaller settling time, smaller rising time and minimum error in steady state. Furthermore, the fuzzy controller provides good results for large load variations. The frequency output of the controller has been validated with experimental measurements of AWM90-X.